White supremacist violence: understanding the resurgence and stopping the spread - Van Brunt, Brian (Routledge, 2023)
"White Supremacist Violence is a powerful resource for education and mental health professionals who are developing the tools and skills needed to slow the progress of the fast-growing hate movement in the United States. Chapters immerse the reader in a hybrid of research, historical reviews, current events, social media and online content, case studies, and personal experiences. The first half of the text explores the ways in which individuals become increasingly indoctrinated through the exploitation of cognitive openings, perceptions of real or imagined marginalization, and exposure to political rhetoric and manipulation, as well as an examination of social media and commerce sites that create a climate ripe for recruitment. The second half of the book walks the reader through three cases studies and offers treatment considerations to assist mental-health professionals and those developing education and prevention-based programming. White Supremacist Violence gives readers useful perspectives and insights into the white supremacy movement while offering clinicians, threat-assessment professionals, and K-12 and university educators and administrators practical guidance on treatment and prevention efforts"--